History of Minority Islam in Cambodia, Laos and Vietnam and Its Development in Contemporary Times - Hidayat, Asep Achmad; Solehudin, Solehudin; Suprianto, Sopian; Wahyuni, Supi Septia; Sopiah, Eva (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2025)
This research discusses the history of the entry of Islam, the development of Muslim communities, and the challenges faced by Muslim communities in the Indochina region, which includes Cambodia, Laos, and Vietnam. Despite being a minority, the region's Muslim community has a rich history, from the role of the Kingdom of Champa as a center for the spread of Islam to the influence of colonialism and political conflicts, such as the Khmer Rouge regime in Cambodia and forced assimilation in Vietnam. The methodology used in this study is a qualitative approach with a library research method. Data is collected from a variety of historical sources, such as academic literature, colonial archives, reports of international institutions, and local historical documents related to the development of Islam. The analysis is conducted descriptively and historically to uncover the roles, transformations, and challenges of the Muslim community over time. The results of the study show that the Muslim community in Indochina faces various dynamics, ranging from cultural integration, political pressure, to identity marginalization. This research confirms the importance of preserving Islamic cultural heritage and manuscripts, as well as the need for international support to strengthen Muslim communities as part of social diversity in the Southeast Asian region.